Peran Madin Hidayah sebagai Media Dakwah dalam Meningkatkan Baca Santri - Nasrul Syarif; Wasito (Universitas Islam Tribakti Lirboyo Kediri, 2021)
Pesantren is the best means to improve students' reading. The reason is that the life of students in Islamic boarding schools is dominated by learning and da'wah. However, previous studies show that students' reading interest is also very low. In Lirboyo, the students' interest is dominated by memorization, while only a few are interested in enriching their reading. In this context, this research is here to see the phenomenon of Mading Hidayah's role in increasing the reading interest of MHM Lirboyo students, Kediri City. This study uses a qualitative method. Data were analyzed using the descriptive analysis method. The results showed that Mading Hidayah is a mass media managed independently by the students who have a strategic role and function if managed properly and can be used as a propaganda medium to increase students' reading interest.